مستقبل التعليم في إندونيسية بين الرجاء والتمني - Sufrin Efendi Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2019)
Spring Arab affets many education, invirenment in Arab. This Effect in not only experienceed by inding enous but also felt by students who comes from another countries that study at Arab. Arab countries are the best in Islamic knowledge, culture and civilization, but Arabian dind’t care about it because their focus to politics, sosial. And Indonesian mission as a center of khowlagde and aducation in the world. Especially in Islamic Student, Inshaallah this mission will improve in Indonesia. To prove this mission, Indonesian goverment should prepare, 1) Professional teacher, 2) Modern Library. Besid its weakness Indonesia also has strength they are، 1) Indonesia has the biggets muslim population in the world, 2) Indonesia population at fouth lever in the world, 3) In democrary Indonesia at third level in the world, 4) Indonesia has the largest Islamic education Institution, 5) Moslem in Indonesia are moderat. All teh above point will make Indonesia as a center of Islami education in the world. It mens that Indonesia as reference and model in Islamic Studies, next time people will come to Indonesia for studing and and sharing khowladge from Indonesia teacher. They also called Indoensia as a symbol of Islamic studies in teh world.